2013
DOI: 10.1515/jpm-2013-0147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sex on perinatal mortality and morbidity in twins

Abstract: Objective: Twin studies offer opportunities to investigate mechanisms underlying sex-associated differences in perinatal outcomes. The objective of the study was to investigate sex-related differences in perinatal complications. Study design: A cohort of 16,045 twin pregnancies -32,090 twins -was explored for obstetric complications, perinatal and infant mortality, and neonatal morbidities. Results: Twin pregnancies with a female fetus had an increased risk for preeclampsia, but otherwise there were no pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
30
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 25 publications
9
30
1
6
Order By: Relevance
“…The present study agreed with previous twin studies reporting higher mortality for male-male than for female-female twins [1517]. However, we found that within OS twin pairs, sex-related differences in mortality were much less pronounced with no significant mortality differences between girls and boys, also consistent with earlier reports [17,32].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study agreed with previous twin studies reporting higher mortality for male-male than for female-female twins [1517]. However, we found that within OS twin pairs, sex-related differences in mortality were much less pronounced with no significant mortality differences between girls and boys, also consistent with earlier reports [17,32].…”
Section: Discussionsupporting
confidence: 93%
“…However, we found that within OS twin pairs, sex-related differences in mortality were much less pronounced with no significant mortality differences between girls and boys, also consistent with earlier reports [17,32]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Various studies have focused on gender-specific outcomes in different conditions, and it has been found that spontaneous abortions and preterm deliveries [17][18][19], as well as respiratory morbidity and neonatal mortality in twin pregnancies, are more common in male infants [20]. Carlsen et al analyzed fetal and neonatal morbidity rates in a 38-year period, and the overall mortality rates were always higher in male infants [21].…”
Section: Discussionmentioning
confidence: 99%
“…Различия в биологической эффективности прогестерона при многоплодной и одноплод-ной беременности могут быть связаны с преоб-ладанием в патогенезе преждевременных родов при двойне чрезмерного растяжения мышечных волокон, в то время как при одноплодной бере-менности основная роль отводится инфекцион-но-воспалительным процессам [55].…”
unclassified